Impact of COVID-19 on tourism 2020 - Kovalska Lesia; Ковальська Леся; Chorna Lyubov; Чорна Любов; Shchuka Halyna; Щука Галина; Scsuka Halina; Polova Lesya; Польова Леся; Mykhailyuk Vitaliy; Михайлюк Віталій (Альфа-ПІК, 2021)
Abstract. The article states that the tourism image of the titan countries of the tourism business has lost its position in international and domestic markets against the background of the deployment of an infectious disease - Covid-19, which in scale and number of victims went into a pandemic. A number of measures to minimize economic and financial defaults in the tourism industry are presented on the example of the countries of the Republic of Poland and Bulgaria. At the international level, mass events, competitions, contests, etc. have been abolished and postponed indefinitely, vehicle restrictions have been restricted, hotels and entertainment establishments have been suspended, the movement of citizens has been restricted and strict quarantine measures have been carried out within individual countries. The authors found that the pandemic was hit hard by countries whose economies depend on the service sector, including the tourism industry. It is statistically presented that Ukraine, whose economy does not depend on the development of tourism, can get revenge on the domestic tourism market, which is associated with the forced suspension of international migration flows, passenger traffic and the initial development of active tourism and ecotourism. And thanks to the introduction of quarantine measures in the internetization and modernization of communications to present the unique natural heritage of the country and emphasize the quality of the tourist product. It was found that the introduction of quarantine measures on the one hand led to the minimization of diseases during the pandemic, and on the other - to the economic collapse (the work of enterprises was suspended, a significant number of migrant workers returned home). At the same time, economic stagnation in some countries has also led to the greening of the environment, such as China, Spain, Italy and others.

Резюме. У статті констатовано, що туристичний імідж країн-титанів туристичного бізнесу втратив свої позиції на міжнародному та внутрішньому ринках на тлі розгортання інфекційної хвороби – Covid-19, яка за масштабом ураженості та кількістю жертв перейшла у пандемію. Представлено ряд заходів щодо мінімалізації економічного та фінансового дефолту у туристичній галузі на прикладі Польщі та Болгарії. На міжнародному рівні скасовано й перенесено на невизначений термін заходи, конкурси, змагання тощо, які носять масовий характер, проведені обмеження транспортних засобів, призупинено функціонування готелів та закладів розваг, обмежено пересування громадян й проведено жорсткі карантинні заходи в межах окремих країн. Авторами встановлено, що нещівного удару пандемії зазнали країни, економіка яких залежить від сфери обслуговування, в тому числі від туристичної галузі. Статистично представлено, що Україна, економіка якої не залежить від розвитку туризму, може отримати реванш на внутрішньому туристичному ринку, що пов’язано із примусовим призупиненням міжнародних міграційних потоків, пасажироперевезень. А завдяки введенню карантинних заходів при інтернетизації та модернізації зв’язку представити унікальну природну спадщину країни й зробити акцент на якості туристичного продукту. Виявлено, що впровадження карантинних заходів з одного боку призвело до мінімалізації захворювань під час пандемії, а з іншого – до економічного колапсу (призупинено роботу підприємств, значна кількість емігрантів-заробітчан повернулися на батьківщину). В той же час економічна стагнація в окремих країнах також призвела до екологізації довкілля, наприклад, в Китаї, Іспанії, Італії тощо.

Резюме. В статье констатировано, что туристический имидж стран-титанов туристического бизнеса потерял свои позиции на международном и внутреннем рынках на фоне развертывания инфекционной болезни - Covid-19, которая по масштабу пораженности и количеством жертв перешла в пандемию. Представлен ряд мер по минимизации экономического и финансового дефолта в туристической отрасли на примере стран Республики Польша и Болгарии. На международном уровне отменено и перенесено на неопределенный срок мероприятия, конкурсы, соревнования и т.д., которые носят массовый характер, проведенные ограничения транспортных средств, приостановлено функционирование гостиниц и заведений развлечений, ограничено передвижение граждан и проведения жесткие карантинные мероприятия в рамках отдельных стран. Авторами установлено, что от значительного удара пандемии потерпели страны, экономика которых зависит от сферы обслуживания, в том числе от туристической отрасли. Статистически представлено, что Украина, экономика которой не зависит от развития туризма, может получить реванш на внутреннем туристическом рынке, что связано с принудительным приостановлением международных миграционных потоков, пассажироперевозок и первично заложенных основными развития внутреннего активного туризма и экотуризма. А благодаря введению карантинных мероприятий при интернетизации и модернизации связи представить уникальную природное наследие страны и сделать акцент на качестве туристического продукта. Обнаружено, что внедрение карантинных мероприятий с одной стороны привело к минимизации заболеваний во время пандемии, а с другой - к экономическому коллапсу (приостановлена работа предприятий, значительное количество эмигрантов-работников вернулись на родину). В то же время экономическая стагнация в отдельных странах также привела к экологизации окружающей среды, например, в Китае, Испании, Италии и др.
Вплив COVID-19 на туризм-2020
Влияние COVID-19 на туризм-2020
Keywords: Covid-19; pandemic; tourism; Ukraine; service sector; tourism industry; пандемія; туризм; Україна